Achieving Milestones as a Prerequisite for Proceeding With a Clinical Trial. (June 2018) - Mickle, Angela M.; Maybrier, Hannah R.; Winter, Anke C.; McKinnon, Sherry L.; Torres, Brian A.; Lin, Nan; Lenze, Eric J.; Stark, Susan; Muench, Maxwell R.; Jacobsohn, Eric; Inouye, Sharon K.; Avidan, Michael S.; et al.
Abstract : BACKGROUND: Although the National Institutes of Health (NIH) invests $30 billion in research annually, many funded studies fail to generate results that can inform practice. The National Institutes of Health introduced a phased funding mechanism as one potential solution. Study-specific milestones are established for an initial pilot phase. We assess the utility of this phased approach through the ongoing Electroencephalography (EEG) Guidance of Anesthesia to Alleviate Geriatric Syndromes (ENGAGES) pragmatic clinical trial. The hypothesis of the trial is that EEG guidance of general anesthesia, through prevention of EEG suppression, can decrease postoperative delirium and its downstream negative sequelae. METHODS: In collaboration with study stakeholders, we identified critical milestones for the ENGAGES study, with themes common to many clinical trials. These themes include: regulatory tasks; enrollment targets; feasibility and impact of study intervention; primary outcome incidence; measurement reliability of primary outcome; and follow-up. Progress in achieving the milestones was assessed at regular intervals during the pilot phase by ENGAGES investigators, a National Institute on Aging program officer, and a nonpartisan research organization (Westat). RESULTS: Regulatory tasks, including institutional review board approval, infrastructure establishment, and trial registration, were completed on schedule. A total of 117 patients were randomized, exceeding the target by 51. The EEG-guided protocol was successfully implemented, and a relevant effect on anesthetic practice was demonstrated (decrease in median age–adjusted minimum alveolar anesthetic concentration from 0.93 to 0.78 [ P < .001] and increase in median proportion of zero EEG suppression time from 87% to 94% [ P < .01]). Nearly all patients (115 of 117, 98.3%) were assessed for delirium using the Confusion Assessment Method, and the delirium incidence was similar (28.1%; 95% CI, 20%–37%) to the estimate (25%) used for the sample size calculation. Good interrater reliability of delirium assessment was demonstrated ( κ = 0.94 [95% CI, 0.86–1]). Finally, 1-month follow-up vital status data were obtained for 96.9% of patients, with 85.7% of patients completing at least 1 survey. CONCLUSIONS: With the ENGAGES trial, we demonstrated that key milestones can be identified and progressively assessed during a pilot phase. Success in attaining appropriate milestones hypothetically predicts meaningful completion of a study, and can provide justification for proceeding beyond a pilot phase. The impact of this phased approach on return on investment and scientific yield requires additional study.